Triglyceride to high-density lipoprotein cholesterol ratio is associated with increased mortality in older patients on peritoneal dialysis - Xiaojiang Zhan (Lipids in Health and Disease, 2019)
Abstract Background The triglyceride (TG) to high-density lipoprotein cholesterol (HDL-C) ratio (TG/HDL-C) has been suggested as a simple method to identify unfavorable cardiovascular (CV) outcomes in the general population. The aim of this study was to investigate the association between the TG/HDL-C ratio and all-cause and CV mortality in peritoneal dialysis (PD) patients. Methods We retrospectively analyzed patients on PD from November 1, 2005, to February 28, 2017, with a follow-up period lasting until May 31, 2017. The main outcomes were all-cause and CV mortality. Results Among the 973 PD patients, the mean age was 49.67 ± 14.58 (y). During a median follow-up period of 27.2 months (IQR = 13.4–41.5 months), 229 (23.5%) patients died, with 120 (12.3%) dying as a result of CV diseases. The median serum TG/HDL-C ratio was 1.11 (IQR = 0.71–1.80). In a multivariate Cox regression analysis, patients with higher TG/HDL-C ratio levels (tertile 3) had a higher incidence of CV mortality (adjusted HR = 2.12; 95% CI: 1.21–3.72; P = 0.009) and all-cause mortality (adjusted HR = 2.08; 95% CI: 1.37–3.14; P = 0.001) compared to patients in tertile 1. These associations persisted after excluding the patients who have already taken lipid-lowering medications. For older patients (> 60 years), each 1-unit higher baseline TG/HDL-C level was associated with a 48% (95% CI: 1.06–2.07; P = 0.021) increased risk of all-cause mortality and a 59% (95% CI: 1.03–2.45; P = 0.038) increased risk of CV mortality; however, this association was not observed in patients ≤60 years of age. Conclusions A higher serum TG/HDL-C ratio was an independent predictor of all-cause and CV mortality in PD patients. Furthermore, an elevated TG/HDL-C ratio was significantly associated with higher all-cause and CV mortality in older PD patients.